2008
DOI: 10.1097/qai.0b013e3181806bf1
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Efficacy of Modified Directly Observed Antiretroviral Treatment in Mombasa, Kenya: A Randomized Trial

Abstract: M-DOT increased adherence, most notably among depressed participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 49 publications
8
92
0
Order By: Relevance
“…13,26,[29][30][31][32] When we examined study reporting of methodological features in full-text studies and where authors provided information (n=7), we found moderate reporting of important methodological issues. Six studies reported sequence generation, 13,[22][23][24][25]28 three reported allocation concealment, 13,24,25 none reported masking of study analysts, and four reported results as a full intention-totreat analysis. 13,22,27,28 Five studies reported less than 20% of participants lost to follow-up.…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…13,26,[29][30][31][32] When we examined study reporting of methodological features in full-text studies and where authors provided information (n=7), we found moderate reporting of important methodological issues. Six studies reported sequence generation, 13,[22][23][24][25]28 three reported allocation concealment, 13,24,25 none reported masking of study analysts, and four reported results as a full intention-totreat analysis. 13,22,27,28 Five studies reported less than 20% of participants lost to follow-up.…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…A further seven studies were included from article bibliographies and conference abstracts, and 78 were excluded because they did not meet our inclusion criteria (one because the author did not respond so we failed to secure suffi cient data 21 ). Overall, 12 studies were included for analysis (table 1): six from the USA, 22,23,27,[30][31][32] fi ve from Africa (Mozambique, 24 Kenya, 25 Nigeria, 26 and South Africa 13,29 ), and one multicentre study from the USA and South Africa. 28 All full-text papers and abstracts were published in English.…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…The effects of interventions are summarized in Table 1 46,48,54,62,64,[66][67][68]73,81 Details of the latter studies serve to illuminate the most potent interventions among the studies in this review. Chung and colleagues 66 conducted a randomized controlled factorial design trial in 361 treatment naïve HIV-infected adults in Nairobi, Kenya initiating ART.…”
Section: Effects Of Interventionsmentioning
confidence: 99%
“…Five of the 33 interventions (15%) tested in high income settings were successful, 46 48,54,62,64 compared to four of eleven (36%) in low income settings. [66][67][68]73 Effects by theoretical framework. Five of the 30 (17%) studies with an explicit theoretical framework were successful in improving both adherence and clinical outcomes.…”
Section: Effects Of Interventionsmentioning
confidence: 99%
“…In a 2004 randomized trial to assess a modified version of DOT (m-DOT); 234 HIV infected adults located in Mombasa, Kenya receiving antiretroviral therapy were visited by a nurse twice weekly to observe ingestion of their medications (Sarna et al, 2008). Adherence in these m-DOT patients improved 480% (P< 0.001), with final adherence levels reported at 82%.…”
Section: Other Directly Observed Therapy Findingsmentioning
confidence: 99%